Squamanitaceae and three new species of Squamanita parasitic on Amanita basidiomes - Jian-Wei Liu; Zai-Wei Ge; Egon Horak; Alfredo Vizzini; Roy E. Halling; Chun-Lei Pan; Zhu L. Yang (IMA Fungus)
Abstract The systematic position of the enigmatically mycoparasitic genus Squamanita (Agaricales, Basidiomycota) together with Cystoderma, Phaeolepiota, Floccularia, and Leucopholiota is largely unknown. Recently they were recognized as Squamanitaceae, but previous studies used few DNA markers from a restricted sample of taxa from the family and lacked a formal taxonomic treatment. In this study, with newly generated sequences of the type of the genus Squamanita, S. schreieri, and several additional species of the family, the phylogeny is reinvestigated with a concatenated (18S-5.8S-nrLSU-RPB2-TEF1-α) dataset. This study reveals that Cystoderma, Phaeolepiota, Squamanita, Floccularia, and Leucopholiota are a monophyletic clade with strong statistical support in Bayesian analysis and form Squamanitaceae. Phaeolepiota nested within Cystoderma; Squamanita, Leucopholiota, and Floccularia clustered together as two monophyletic subclades; and Squamanita was present as a monophyletic clade with strong statistical support in both Maximum Likelihood and Bayesian analyses. The family name Squamanitaceae is formally emended and a detailed taxonomic treatment is presented to accommodate the five genera. Meanwhile, another concatenated (18S-ITS-nrLSU-RPB2-TEF1-α) dataset is used to investigate phylogenetic relationships and species delimitation in Squamanita. Our data indicates that “S. umbonata” from the Northern hemisphere forms two species complexes, one complex includes six specimens from North America, Europe, and East Asia, the other includes two specimens from Central America and North America respectively. Futhermore, species of Squamanita can parasitize species of Amanita, besides other fungal species. Squamanita mira parasitizes A. kitamagotake (A. sect. Caesareae), while S. orientalis and S. sororcula are parasites of species belonging to the A. sepiacea complex (A. sect. Validae). “Squamanita umbonata” from Italy occurs on A. excelsa (A. sect. Validae). Three new species of Squamanita from East Asia, viz. S. mira, S. orientalis and S. sororcula are documented with morphological, multi-gene phylogenetic, and ecological data, along with line drawings and photographs, and compared with similar species. A key for identification of the global Squamanita species is provided.